Modelling heterogeneous economies - robustness vs. flexibility - Koloch, Grzegorz; Kamiński, Bogumił; Żbikowski, Mateusz; Antosiewicz, Marek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
In this paper we present and compare two different modelling paradigms which compete within the field of heterogeneous agent macroeconomics: a dynamic stochastic general equilibrium approach, which is considered mainstream, and an agent-based approach. We concentrate on methodological aspects and provide an at-hand comparison of the two approaches. Our main conclusion is that, unlike in the case of DSGE, the development of ABMs is impeded by the lack of a baseline, reference specification. The development of such would result in synergy between the research agendas of individual researchers. However it may be difficult, if not impossible, to obtain one since in the ABM method decision or policy functions constitute degrees of freedom and a reference specification would have to abstract from pinning them down. Therefore, even with such a specification available, it can be impossible to produce a high-level theory – stylized predictions, which would be qualitatively robust over the discretionary implementations of particular mechanisms within the model. An issue of whether the assumptions of the DSGE paradigm reflect an optimal trade-off between the robustness of the predictions and the flexibility in the specification remains at this time undecided. We believe this question will be answered when commonly available computational technology will allow for full rationality within the ABM framework, which, in principle, is possible
Argumenta Oeconomica, 2017, Nr 2 (39), s. 193-212
Keywords: heterogeneous agent macroeconomic modelling; dynamic stochastic general equilibrium; agent based modelling